2004
DOI: 10.1016/s0021-9975(03)00083-5
|View full text |Cite
|
Sign up to set email alerts
|

Neurotropism of Swine Haemagglutinating Encephalomyelitis Virus (Coronavirus) in Mice Depending upon Host Age and Route of Infection

Abstract: Mice aged 1, 4 or 8 weeks were inoculated with haemagglutinating encephalomyelitis virus (HEV), strain 67N, by the intracerebral (i.c.), intranasal (i.n.), intraperitoneal (i.p.), subcutaneous (s.c.), intravenous (i.v.) or oral route, with different doses. In 1-week-old mice, mortality and mean time to death were mostly the same regardless of the inoculation route, except for the oral route, which appeared to be the least effective. The virus killed 4-week-old mice readily by all routes of inoculation except t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 13 publications
2
27
0
1
Order By: Relevance
“…In the present study, PRV infected nerve cells and nonneuronal cells, but HEV antigen was found only in nerve cells. These in vitro findings were consistent with previous in vivo studies in which PRV antigens were found in astrocytes and nerve cells [3,9], whereas HEV particles could be found in nerve cells but were not detected in glial cells and infiltrating cells [11,12,23]. Based on these in vivo and in vitro findings, infectivity of HEV may be more strictly restricted to nerve cells than PRV and rabies virus, for which non-neuronal cells may support viral entry and replication [19].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, PRV infected nerve cells and nonneuronal cells, but HEV antigen was found only in nerve cells. These in vitro findings were consistent with previous in vivo studies in which PRV antigens were found in astrocytes and nerve cells [3,9], whereas HEV particles could be found in nerve cells but were not detected in glial cells and infiltrating cells [11,12,23]. Based on these in vivo and in vitro findings, infectivity of HEV may be more strictly restricted to nerve cells than PRV and rabies virus, for which non-neuronal cells may support viral entry and replication [19].…”
Section: Discussionsupporting
confidence: 90%
“…The virus was first isolated in Canada from the brains of suckling piglets [25], and causes encephalomyelitis or vomiting and wasting disease in suckling piglets [6,25]. In previous in vivo studies using piglets and mice, HEV has been suggested to invade the central nervous system via the peripheral nervous system (neural spread) [2,11,25,32,33]. However, the neural spread of HEV has not been demonstrated by in vitro studies.…”
Section: Swine Hemagglutinating Encephalomyelitis Virus (Hev)mentioning
confidence: 99%
“…), and productive infection of the contralateral primary motor cortex at day 4 p.i. (Hirano et al, 1993(Hirano et al, , 1998(Hirano et al, , 2004Bai et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In that latter case, neuroinvasion depends on a number of variables such as the route of inoculation and the age of the mice (Yagami et al, 1986;Hirano et al, 1990;. As for the SARS-CoV in mice, HEV induced a poor inflammatory reaction in CNS (Hirano et al, 2004) and unlike HCoV-OC43-infected neurons (Jacomy & Talbot, 2003), HEV-infected cells showed no cytopathological changes.…”
Section: Swine Coronaviruses (Hev)mentioning
confidence: 99%